2021
DOI: 10.1186/s12866-020-02070-5
|View full text |Cite
|
Sign up to set email alerts
|

Microbiology of secondary infections in Buruli ulcer lesions; implications for therapeutic interventions

Abstract: Background Buruli ulcer (BU) is a skin disease caused by Mycobacterium ulcerans and is the second most common mycobacterial disease after tuberculosis in Ghana and Côte d’Ivoire. M. ulcerans produces mycolactone, an immunosuppressant macrolide toxin, responsible for the characteristic painless nature of the infection. Secondary infection of ulcers before, during and after treatment has been associated with delayed wound healing and resistance to streptomycin and rifampicin. However, not much is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…The clinical samples were processed according to Gyamfi et al (2021) . The swabs were processed for culture and DNA extraction.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The clinical samples were processed according to Gyamfi et al (2021) . The swabs were processed for culture and DNA extraction.…”
Section: Methodsmentioning
confidence: 99%
“…The disease causes extensive necrosis of the skin and underlying tissues which can lead to severe ulceration if treatment is delayed ( Johnson et al, 2005 ). Even though BU is not fatal, the associated lengthy hospital stays during treatment, risk of secondary infections, permanent deformities and joint contractures, cost of surgery, and social stigma often result in a dire social and economic burden on the families of affected individuals ( Grietens et al, 2008 ; Adamba and Owusu, 2011 ; Gyamfi et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The combination of rifampicin, levofloxacin, and clarithromycin is used in Japan [ 9 ]. Microbiological studies on patients with BU revealed that there is additional colonization with Staphylococcus spp., Bacillus spp., and Pseudomonas spp., which can delay recovery [ 49 ]. Since the lesions are painless, patients frequently seek medical attention in later stages, when antibiotic therapy is less effective.…”
Section: Current Buruli Ulcer Treatment and The Main Challenges To Co...mentioning
confidence: 99%
“…Time to complete wound closure is a crucial endpoint for clinicians managing BU wounds. Buruli lesions treated with antibiotics may heal rapidly or enlarge due to breakdown of necrotic tissue, experience a paradoxical reaction, or develop secondary bacterial infection; these can delay wound healing [3] , [7] , [8] , [9] , [10] , [11] . Establishing the time to healing or rate of healing at patient presentation can be a challenge highlighting the need for tools to guide critical care decisions.…”
Section: Introductionmentioning
confidence: 99%